The hidden reefs in foreign language teaching: on the presence and instruction of discourse markers in textbooks for teaching Polish as a foreign language - Toffel, Sandra (Glottodidactica, 2019)
Discourse markers (DMs), represented by words and phrases such as but, you know, moreover, have for many years been a widely discussed topic in linguistics in Poland and abroad. However, no attention has been paid yet to DMs in teaching Polish as a foreign language (PFL). The paper explores this neglected issue by analysing the modes of presentation of DMs in the three most popular series of textbooks for teaching PFL (levels A1-B1). The textbooks were analysed manually to identify DMs and the ways in which they are taught. The results show that the textbooks differ in the number of DMs appearing in them. However, four common problematic aspects of the instruction of DMs in the analysed textbooks were identified: translation of DMs, usage of homographs of DMs, the mechanical nature of exercises and lack of sufficient input